A novel neuromodulation strategy to enhance the prefrontal control to treat pain. (April 2019) - Zhou, Haocheng; Zhang, Qiaosheng; Martinez, Erik; Dale, Jahrane; Robinson, Eric; Huang, Dong; Wang, Jing
Effective pharmacological treatment options for chronic pain remain very limited, and continued reliance on opioid analgesics has contributed to an epidemic in the United States. On the other hand, nonpharmacologic neuromodulatory interventions provide a promising avenue for relief of chronic pain without the complications of dependence and addiction. An especially attractive neuromodulation strategy is to optimize endogenous pain regulatory circuits. The prefrontal cortex is known to provide top-down control of pain, and hence neuromodulation methods that selectively enhance the activities in this brain region during pain episodes have the potential to provide analgesia. In this study, we designed a low-frequency (2 Hz) electrical stimulation protocol to provide temporally and spatially specific enhancement of the prefrontal control of pain in rats. We showed that low-frequency electrical stimulation of the prelimbic region of the prefrontal cortex relieved both sensory and affective responses to acute pain in naive rats. Furthermore, we found that low-frequency electrical stimulation of the prefrontal cortex also attenuated mechanical allodynia in a rat model of chronic pain. Together, our findings demonstrated that low-frequency electrical stimulation of the prefrontal cortex represents a promising new method of neuromodulation to inhibit pain.